Drag and lift measurements of solid sports balls in still air - Kensrud, J. R.; Smith, L. V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
The following article considers lift and drag measurements of solid sports balls propelled through still air in a laboratory setting. The balls traveled at speeds ranging from 26 to 134 m/s with spin rates up to 3900 r/min. Light gates measured the speed and location of the balls at two locations from which lift and drag values were determined. Ball roughness varied from polished to rough surface protrusions, that is, seams as high as 1.5 mm. Lift and drag were observed to depend on speed, spin rate, surface roughness, and seam orientation. A drag crisis was observed on smooth balls as well as non-rotating seamed balls with seam heights less than 0.9 mm. The drag coefficient of approximately 0.42 was nearly constant with speed for spinning seamed balls with seam height greater than 0.9 mm. The still air drag coefficient of smooth balls was comparable to wind tunnel drag at low speeds (Re < 2 x 10^5) and higher than wind tunnel results at high speeds (Re > 2 x 10^5). The lift and drag coefficients of spinning balls increased with increasing spin rate. The lift coefficient of baseballs was not sensitive to ball orientation or seam height.